Protein expression during spatialleaming in the Morris water maze in mice - Perumal Ramasamy; Zahurin Mohd; Charles S. Vairappan (Universiti Malaysia Sabah, 2010)
Learning and memory are two Important physiological and biochemical processes that enable a living organism to adapt to the challenging environment During learning there are changes in behaviour relative to experience and consequently leading to changes in memory. The mechanism of learning and memory involves synaptic plastidty and longterm potentiation. These processes involve changes in the protein chemistry in different parts of brain and are believed to be dependent on synthesis of new protein which is the basis of memory. Memory as a whole cellular protein synthetic mechanism which is consolidation in the hippo campus. Memory formation occurs via a number of signalling pathways associated with the activation of many synaptic plastidty-refated proteins in the brain, such as N-Methyl-D-aspartlc add receptor, ca2+/calmodulin dependent protein kinase II (caMKII), mitogen-activated protein klnases (MAPKs),... The hippocampus 15 a part of brain that plays an Important role In spatial cognition and memory. This study 15 to Investigate the role of the hippo campus in the formation of the spatlalleaming and memory in the Morris water maze In mice as an experimental animal. The mice were sacrificed by cervical dislocation and total protein In the hippo campus was extracted. During this study the protein expression involved in the learning process, comparison and Identification of expressed protein levels in the brain region of control and trained mice were done. The protein expressed was estimated by using the two dimensional gel-electrophoresls based on separation of the various protein according to their lsoelectric points and molecular weight. 26 spots were identified with 1.2 Fofd increased with a significant P<O.05. the protein expressed were estimated twice and there was a significant increase in the level of (P<O.05). These spots were analysed by using LCIMS Mass Spectromeby. Based on LCIMS Mass Spectrometry the proteins involved in learning were categOrised in to neurogenesls (Cytoskeletal), carbohydrate metabolism, signal transduction and transport, such as: a-Intemexln, fructosebisphosphate, dihydropyramldlnase-related protein 2, voltage-dependent anion channel ..in summary, by using a proteomlcs approach, this study explained that training affect a difference network of proteins pertaining to energy metabolism and synaptic plastidty in the hippo campus, a brain region central to cognitive function. Further study can help to identify the spatial protein and path way of learning and memory mechanism.